Metabolism and pharmacokinetics of the anti-varicella-zoster virus agent 6-dimethylaminopurine arabinoside. - Lambe, C U (1992)
The metabolism of 6-dimethylaminopurine arabinoside (ara-DMAP), a potent inhibitor of varicella-zoster virus replication in vitro, was studied in rats and cynomolgus monkeys. Rats dosed intraperitoneally or orally with ara-DMAP excreted unchanged ara-DMAP and one major metabolite, 6-methylaminopurine arabinoside (ara-MAP), in the urine. They also excreted allantoin and small amounts (less than 4% of the dose each) of hypoxanthine arabinoside (ara-H) and adenine arabinoside (ara-A). The relative amount of each urinary metabolite excreted remained fairly constant for intraperitoneal ara-DMAP doses of 0.3 to 50 mg/kg of body weight. Rats pretreated with an inhibitor of microsomal N-demethylation, SKF-525-A, excreted more unchanged ara-DMAP and much less ara-MAP than did rats given ara-DMAP alone. Rats pretreated with the adenosine deaminase inhibitor deoxycoformycin excreted more ara-MAP and much less ara-H and allantoin. ara-MAP was shown to be a competitive alternative substrate inhibitor of adenosine deaminase (Ki = 16 microM). Rats given ara-DMAP intravenously rapidly converted it to ara-MAP and purine metabolism end products; however, ara-A generated from ara-DMAP had a half-life that was four times longer than that of ara-A given intravenously. In contrast to rats, cynomolgus monkeys dosed intravenously with ara-DMAP formed ara-H as the major plasma and urinary end metabolite. Rat liver microsomes demethylated ara-DMAP much more rapidly than human liver microsomes did. ara-DMAP is initially N-demethylated by microsomal enzymes to form ara-MAP. This metabolite is further metabolized by either adenosine deaminase, which removes methylamine to form ara-H, or by microsomal enzymes, which remove the second methyl group to form ara-A.